The GT1-TPS Structural Domain Protein From Haemonchus contortus Could Be Suppressive Antigen of Goat PBMCs - Wen, Zhaohai; Aleem, Muhammad Tahir; Aimulajiang, Kalibixiati; Chen, Cheng; Liang, Meng; Song, Xiaokai; Xu, Lixin; Li, Xiangrui; Yan, Ruofeng (Frontiers in Immunology, 2022)
Trehalose phosphate synthase (TPS) is one of the keys to the synthesis of trehalose, an enzyme that is not present in mammals but is critical to the viability of a wide range of lower organisms because trehalose is a key metabolite. However, almost nothing is known about the function of Hc-TPS (GT1-TPS structural domain protein from Haemonchus contortus). In the present study, the Hc-TPS gene was cloned and the recombinant protein (rHc-TPS) was expressed and purified. The qPCR results showed that Hc-TPS was transcribed at different developmental stages of Haemonchus contortus (H. contortus), with higher levels of transcription at the molt and embryo stages. Immunofluorescence analysis showed that Hc-TPS was widely distributed in adults, but the expression was mainly localized on the mucosal surface of the intestine and in the embryos of female worms. The impacts of rHc-TPS on PBMCs cell proliferation, nitric oxide (NO) generation, transcriptional expression of cytokines and related pathway molecules were examined by co-incubating rHc-TPS with goat PBMCs. The results showed that rHc-TPS significantly inhibited PBMCs proliferation and NO secretion in a dose-dependent manner. We also found that rHc-TPS activated the IL-10/STAT3/SOCS3 axis and significantly promoted SOCS3 expression, while inhibiting INF-γ, IL-4, IL-9 and IL-2 pathways. Our findings contribute to understand the procedure elaborate for protection against parasites during host-parasite interactions and also produce new ideas for the progress of new drug targets.